TARIKH DUKHUL AL LUGHAH AL ARABIYYAH WA INTISYARUHA FI INDUNISIA - Ade Dedi Rohayana (Arabic Education Program IAIN Pekalongan, 2016)
As the language of Islam, Arabic has an important position for Indonesian people. There has been no research result which shows when the study of Arabic come, initiated, and developed for the first time. The developed assumption is that Arabic is already known by Indonesian people since Islam is known and adhered by majority of our nation. The aim of this paper is to provide a clear picture of Islamic world related to the history of Arabic language in Indonesia.